Temperament, Character, and Defense Mechanism Changes With Treatment in Depression: A 9-Month Naturalistic Follow-up. Issue 5 (May 2020) - Tabakci, Abdulkadir Sencer; Yildirim, Ejder Akgun; Erkiran, Murat; Aksoy, Umut Mert; Sahan, Halide Erten; Tuna, Ozgecan; Tomruk, Nesrin Buket; Alpay, Nihat
Abstract : Abstract: The aim of this study was to evaluate the changes in temperament, character, and defense mechanisms with the treatment and remission in patients with major depressive disorder. The study was designed as a longitudinal observational follow-up study of patients with repeated measures at 0, 12, and 36 weeks. In baseline comparisons, the major depression group showed higher harm avoidance and novelty seeking scores and lower self-directness and mature defense styles scores compared with healthy controls. In the follow-up, temperament dimensions and neurotic defenses remained unchanged, mature defense styles and self-directness revealed significant increase, and immature defense styles revealed significant decrease. Although there was no significant difference in the defense styles, harm avoidance and novelty seeking scores remained higher in MDD patients compare with healthy controls in 36 weeks. Our findings regarding continuation of hierarchically upward improvement in defense mechanism after the remission may support importance of treatment after remission.